Vpliv pettedenske Interdisciplinarne obravnave pri bolnikih s kronično razširjeno nerakavo bolečino na variabilnost srčne frekvence pri obremenitvenem testiranju in občutenje bolečine - Žen Jurančič, Marijana (Rehabilitacija (Ljubljana), 2017)
Background: Patients with chronic widespread nonmalignant pain syndrome are known to have a disturbance in the regulation of the autonomic nervous system. Their tonus activation of the sympathetic nervous system is increased. The aim of our study was to verify the impact of a five-week interdisciplinary program that includes aerobic training of moderate intensity on the change in variability of heart frequency during stress testing, and the impact on the perception of pain. Methods: Thirty-two patients, who were included in the interdisciplinary program for chronic widespread nonmalignant pain treatment at the University Rehabilitation Institute in Ljubljana during 2014 and 2015, participated in the study. Before the program, they passed the stress testing and completed two psychological questionnaires (Chronic Pain Acceptance Questionnaire and The Pain Catastrophizing Scale). The program included aerobic interval training two times a day, for five weeks. After five weeks of interdisciplinary rehabilitation treatment, the patients were tested again. We analysed maximum heart rate, peak power (W), maximum blood pressure, maximum achieved blood pressure, and LF/HF (n.u.) ratio as a marker of the variability of the heart frequency. We also analysed the results of the psychological questionnaires. Results: The participants were 52 years old on average; 91% were women. For most outcome measures (maximum heart rate, power and oxygen consumption), we observed a statistically significant improvement (p<0.005) after the program. The results of psychological tests showed a significantly lower rate of pain catastrophizing at the end of the program. Participants reported that they were able to calm down easier after the program, they observed less repetitive thoughts about pain and were experiencing more strength in coping with pain. Conclusion: Our results confirm the improvement of aerobic capacity in subjects with chronic widespread nonmalignant pain after the five-week interdisciplinary rehabilitation program. Our results did not confirm changes of heart rate variability. Participants reported higher involvement in daily activities and less catastrophic and intense pain experience after the program.
Keywords: autonomic nervous system; avtonomno živčevje; Chronic Pain; Heart Function Tests; heart rate variability; kronična bolečina; obremenitveno testiranje; Pain Perception; stress testing; veriabilnost srčne frekvence; zaznavanje bolečine